(untitled) - Tidrow, Rob (Hoboken, NJ, 2006)
A handy, full colour guide to tips, tricks, and shortcuts for increasing productivity with a wireless network. This guide offers visual learners useful techniques, full-colour screen shots, a task-oriented approach, and clear explanations on getting the most from their WiFi. Short and quick steps explain how to set up a wireless network, and with brief but important details, offer key tips regarding wireless cards and routers. Targets price conscious, time starved visual learners who are looking for quick and easy solutions to their common technology questions.
Keywords: Wireless communication systems,Hệ thống mạng không dây